2020
DOI: 10.1136/bmjopen-2019-035700
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to the self-management of COPD: a qualitative study from rural Nepal

Abstract: ObjectiveTo understand the facilitators and barriers to the self-management of chronic obstructive pulmonary disease (COPD) in rural Nepal.SettingsCommunity and primary care centres in rural Nepal.ParticipantsA total of 14 participants (10 people with COPD and 4 health care providers) were interviewed.Primary and secondary outcome measure(s)People with COPD and healthcare provider’s experience of COPD self-management in rural Nepal.ResultsFacilitators and barriers affecting COPD self-management in Nepal operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…A number of key barriers both at systems and service delivery levels in Nepal were identified: (1) lack of appropriate NCD policy guidelines, (2) insufficient trained human resources, (3) inadequate logistics, supplies and medications, (4) lack of laboratory facilities, (5) inefficient referral mechanisms and (6) unavailability of systematic recording and reporting systems. These findings corroborate well to the ones reported in another recent study from Nepal 41 as well as other neighbouring countries. 43–45 Studies in Nepal have reported that despite implementation of the WHO PEN package, government’s role has been very limited to providing NCD-related services to combat the growing burden of NCDs in Nepal.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A number of key barriers both at systems and service delivery levels in Nepal were identified: (1) lack of appropriate NCD policy guidelines, (2) insufficient trained human resources, (3) inadequate logistics, supplies and medications, (4) lack of laboratory facilities, (5) inefficient referral mechanisms and (6) unavailability of systematic recording and reporting systems. These findings corroborate well to the ones reported in another recent study from Nepal 41 as well as other neighbouring countries. 43–45 Studies in Nepal have reported that despite implementation of the WHO PEN package, government’s role has been very limited to providing NCD-related services to combat the growing burden of NCDs in Nepal.…”
Section: Discussionsupporting
confidence: 93%
“…Results from our study are in concordance with the findings from other settings, where CHWs expressed the need of capacity building for the prevention and control of NCDs. 41 42 These findings are plausible because in past decades, the CHWs were very much capacitated on maternal and child health activities and were mostly dealing with communicable diseases. However, there had been a shortfall of skilled CHWs and accessibility to health services for combating the growing demands for NCDs services at the peripheral level health facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 In response to this need, we conducted a study among people with COPD between 2018 and 2019 and identified low levels of health literacy, poor self-management practices and various barriers to self-management at patient-family, community and service provider levels. 9 11 12 These findings established the need to engage multiple stakeholders in service design to address the self-management needs of multi-morbid COPD people in Nepal.…”
Section: Introductionmentioning
confidence: 92%